2019
DOI: 10.1111/tbed.13343
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of diarrhoea in piglets caused by novel rotavirus genotype G4P[49] in north‐western district of Bangladesh, February 2014

Abstract: Group A rotavirus (RVA) associated diarrhoea in piglets represents one of the major causes of morbidity and mortality in pig farms worldwide. A diarrhoea outbreak occurred among nomadic piglets in north‐western district of Bangladesh in February 2014. Outbreak investigation was performed to identify the cause, epidemiologic and clinical features of the outbreak. Rectal swabs and clinical information were collected from diarrhoeic piglets (n = 36). Rectal swabs were tested for RVA RNA by real‐time reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Further, we found higher prevalence of rotavirus among children aged <5 years (38.2%, 95% CI: 24%-51%, p = 0.001) than any other meta studies conducted previously (55, 56,[58][59][60][61][62][63][64][65][66][67][68][69]. These data suggest that prevalence of rotavirus is relatively higher than most of the countries and a consistent health problem in Bangladesh (40)(41)(42)(43)(44)(45)(65)(66)(67)(68)(69)(70)(71)(72). This study also suggested a higher prevalence of rotavirus among people of all age groups.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Further, we found higher prevalence of rotavirus among children aged <5 years (38.2%, 95% CI: 24%-51%, p = 0.001) than any other meta studies conducted previously (55, 56,[58][59][60][61][62][63][64][65][66][67][68][69]. These data suggest that prevalence of rotavirus is relatively higher than most of the countries and a consistent health problem in Bangladesh (40)(41)(42)(43)(44)(45)(65)(66)(67)(68)(69)(70)(71)(72). This study also suggested a higher prevalence of rotavirus among people of all age groups.…”
Section: Discussionsupporting
confidence: 48%
“…Rotavirus has remained one of the major causes of children mortality and hospitalization in Bangladesh (43)(44)(45). However, rotavirus vaccination has not been included in the national immunization program in Bangladesh (9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that the prevalence rates of RVA in pigs vary from 3.3% to 67.3% (3). Furthermore, 12 G genotypes (G1-G6, G8-G12, and G26) and 18 P genotypes (P[1]-P [8], P[11], P [13], P [19], P [23], P[25], P [26], P[27], P [32], P[34], and P[49]) of RVA have been detected in pigs (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Until now, the surveillance of pigs RVA remains rare in China.…”
Section: Introductionmentioning
confidence: 99%